2005
DOI: 10.1038/sj.onc.1208922
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β signaling in T cells: roles in lymphoid and epithelial neoplasia

Abstract: Transforming growth factor-b (TGF-b) plays an essential role in regulating the homeostasis of cells in the lymphoid lineage. TGF-b signaling is not required for normal thymopoiesis, but is essential for regulating the expansion, activation, and effector function of the mature CD4 þ and CD8 þ T cells in the peripheral lymphoid organs and target tissues. Recent studies in both mice and humans have elucidated an important and complex role for TGF-b in regulatory T-cell biology. Disruption of TGF-b signaling in T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
1

Year Published

2006
2006
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 129 publications
2
53
0
1
Order By: Relevance
“…Impaired TGF␤ signaling has been implicated in tumorigenesis, including hematopoietic and epithelial malignancies (34,39). Notably, p15 INK4B represents an important effector of TGF␤-induced growth arrest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Impaired TGF␤ signaling has been implicated in tumorigenesis, including hematopoietic and epithelial malignancies (34,39). Notably, p15 INK4B represents an important effector of TGF␤-induced growth arrest.…”
Section: Discussionmentioning
confidence: 99%
“…TGF␤ is an anti-mitogenic cytokine and impaired TGF␤ signaling has been implicated in tumorigenesis (33,34). Notably, p15 INK4B represents an important effector of the anti-growth activity of TGF␤ and is up-regulated by TGF␤.…”
Section: Gfi-1 Functionally Collaborates With C-myc In Repressing Cdkmentioning
confidence: 99%
“…TGF-b inhibits the proliferation and effector function of T cells by inhibiting IL-2 production, but also affects cell-cyclerelated proteins and has additional less well-understood inhibitory actions. 33 The enhanced T-cell proliferation and cytokine expression mediated by the CD28 domain in the chimeric T cells evidently allows for a higher threshold for the effects of TGF-b inhibitory signaling, although it does not completely abrogate sensitivity to this agent.…”
Section: Cd28 Improves Chimeric T-cell Activationmentioning
confidence: 99%
“…7 Studies have shown that TGF-β1 can inhibit effector T-cell proliferation and activation and decrease Th1 and Th2 cell differentiation, while promoting differentiation of Th17 cells. 8,9 Moreover, TGF-β1 is essential for the proliferation of induced T regulatory (Treg) cells 10,11 and up-regulation of FOXP3 12 and plays a role in the immunosuppressive function of Treg due to cytokine secretion or membrane bound expression. 9,11,13 Several functional polymorphisms in TGFB1, the gene encoding for TGF-β1, have been identified, such as a single nucleotide polymorphism (SNP) at codon 10 (coding(c).29T>C, protein(p).L10P) and another at codon 25 (c.75G>C, p.A74P) of exon 1.…”
Section: Introductionmentioning
confidence: 99%